Solar cooker by using solar absorber material for energy production (International Journal of Food and Nutritional Sciences, 2021)
Recently, there has been a lot of interest in the effects of tantalum pentoxide doped with stannic oxide (SnO2) - silver (Ag) salts for solar absorption based on thermal stability. The Rietveld study of the Ta2O5 with SnO2-Ag doping in the absorption of the crystal structure has been examined. The solar box cooker coats the nanocomposite films to increase while maintaining thermal stability above 398F, as accomplished experimentally. The architecture effectively controls the environment while preserving civilisation.